Dynamics of droplet impact on solid surface with different roughness - Tang, Chenglong; Qin, Mengxiao; Weng, Xinyan; Zhang, Xuhui; Zhang, Peng; Li, Jianling; Huang, Zuohua (International journal of multiphase flow, 2017)
•We have for the first time, discussed the effect of Ra thoroughly on the evolution of the non-dimensional droplet spreading diameter β for droplet impacting.•We extended previous work on βmax to accommodate Ra effect and the derived empirical correlations of βmax as a function of Ra show good agreement with both the present and previous experimental data.•The transition from spreading to splashing empirically fitted as a function of the surface roughness, which also shows reasonably good agreement with all the public literature data. This paper reports an experimental investigation on the impact dynamics of droplets (water, decane, ethanol, and tetradecane) onto a flat stainless steel surface, using high-speed microphotography and with a particular interest in the effect of surface roughness on the impact dynamics. Results show that the impacting water droplet spreads on the surface in the form of a rim-bounded lamella and the rim contracts back after reaching the maximum spreading, while this contraction motion is absent for the fuel liquids. With the increase of Weber number (We) and surface roughness, splashing, evidenced by the ejection of secondary droplets, is favored. The droplet spreading, which is characterized by a normalized diameter β, is accelerated with increasing We, while the surface roughness and Ohnesorge number (Oh) tend to slow down the spreading process. Furthermore, the maximum normalized spreading diameter, βmax, depends primarily on the (We/Oh) and the increase in the surface roughness slightly reduces βmax. The transition from spreading to splashing is enhanced with increasing We or Ra or both. An empirical correlation of βmax as a function of the surface roughness was derived based on the present experimental data. In addition, the transition from spreading to splashing can be represented by a critical (We/Oh)1/2, which was fitted as a function of the surface roughness. All the proposed empirical correlations show good agreement with literature data and are believed to be of importance for the spray/wall interaction modelling.